Emotional Intelligence, Self-Regulation, Smartphone Addiction: Which Relationship With Student Well-Being and Quality of Life? - Mascia, Maria Lidia; Agus, Mirian; Penna, Maria Pietronilla (Frontiers in Psychology, 2020)
This study emphasizes the importance of analyzing factors that contribute to student well-being, as a result of the multiplicity of factors that can affect their quality of life (QoL). The literature indicates that, among these factors, emotional intelligence and self-regulation play a central role in influencing adolescents’ psychological and scholastic well-being. Technology is a fundamental aspect of adolescent life but addiction to the use of smartphones is increasing, which can affect both emotional intelligence and self-regulation, and in turn individual well-being and QoL. Therefore, this study explores the role of smartphone use with respect to these aspects. Participants were 215 Italian students attending middle school. By applying partial least squares structural equation modeling (PLS-SEM), the results confirm that self-regulation affects the QoL of students, but its role varies according to the degree of smartphone addiction. In conclusion, we confirm the relevance of the relationship between self-regulation and smartphone addiction in teaching students to be aware of their time spent using smartphones. Emotional intelligence and, in general, self-regulation should be encouraged to support the well-being and QoL of students in their adolescence at school.